2017
DOI: 10.1097/md.0000000000006064
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture therapy in the management of the clinical outcomes for temporomandibular disorders

Abstract: Purpose:The purpose of this study was to evaluate conventional acupuncture therapy in the management of clinical outcomes for temporomandibular disorders (TMD) in adults.Methods:The electronic databases PubMed, EMBASE, Cochrane Central Register of Controlled Trials, and Clinical Trails.gov were searched for reports published until March 31, 2016.Results:Nine eligible studies from 8 publications involving 231 patients were included in the meta-analysis. A comparison of the main outcome of visual analog scale (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 44 publications
3
34
0
3
Order By: Relevance
“…This allows dental practitioners to check for potential herbal -drug interactions before prescribing or initiating treatments. Our present study showed that the participants had been using a variety of TM in treating different conditions for dental care which was consistent with previous studies (Table 4) (2,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). These conditions included gingivitis, toothache, teething, mouth ulcers, sore throat, temporomandibular joint pain, headache, neck pain and nasal decongestion.…”
Section: Use Of Tm In Different Conditionssupporting
confidence: 90%
“…This allows dental practitioners to check for potential herbal -drug interactions before prescribing or initiating treatments. Our present study showed that the participants had been using a variety of TM in treating different conditions for dental care which was consistent with previous studies (Table 4) (2,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). These conditions included gingivitis, toothache, teething, mouth ulcers, sore throat, temporomandibular joint pain, headache, neck pain and nasal decongestion.…”
Section: Use Of Tm In Different Conditionssupporting
confidence: 90%
“…This allows dental practitioners to check for potential herbal -drug interactions before prescribing or initiating treatments. Our present study showed that the participants had been using a variety of TM in treating different conditions for dental care which was consistence with previous studies (Table 4) (2,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). These conditions included gingivitis, toothache, teething, mouth ulcers, sore throat, temporomandibular joint pain, headache, neck pain and nasal decongestion.…”
Section: Use Of Tm In Different Conditionssupporting
confidence: 88%
“…Although several explanations are proposed, the mode of action is not fully clear. It is accepted that the needle penetration causes a micro-inflammation process improving blood circulation and neurotransmitters release, such as serotonin, encephalin, and endorphin, which prevent the propagation of painful stimuli [36][37][38] . In addition, acupuncture promotes muscle relaxation, reestablishing body and mind balance, with recent studies showing benefits in anxiety, depression, and insomnia 6,36,37 .…”
Section: Acupuncturementioning
confidence: 99%